2002
DOI: 10.1126/science.1072802
|View full text |Cite
|
Sign up to set email alerts
|

Orc6 Involved in DNA Replication, Chromosome Segregation, and Cytokinesis

Abstract: Origin recognition complex (ORC) proteins serve as a landing pad for the assembly of a multiprotein prereplicative complex, which is required to initiate DNA replication. During mitosis, the smallest subunit of human ORC, Orc6, localizes to kinetochores and to a reticular-like structure around the cell periphery. As chromosomes segregate during anaphase, the reticular structures align along the plane of cell division and some Orc6 localizes to the midbody before cells separate. Silencing of Orc6 expression by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
190
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(210 citation statements)
references
References 24 publications
9
190
1
5
Order By: Relevance
“…The fact that inactivation of the Orc6 NLS prevents both nuclear localization of Orc6 and cell proliferation demonstrates that nuclear localization of Orc6 is essential to Orc6 function. In the absence of Orc6 function, cells accumulated both in G 1 and in G 2 or M phase, consistent with previous reports that siRNA suppression of either human or Drosophila Orc6 expression retards both DNA replication and cytokinesis (27,28).…”
Section: Nuclear Localization Of Orc6-humansupporting
confidence: 78%
“…The fact that inactivation of the Orc6 NLS prevents both nuclear localization of Orc6 and cell proliferation demonstrates that nuclear localization of Orc6 is essential to Orc6 function. In the absence of Orc6 function, cells accumulated both in G 1 and in G 2 or M phase, consistent with previous reports that siRNA suppression of either human or Drosophila Orc6 expression retards both DNA replication and cytokinesis (27,28).…”
Section: Nuclear Localization Of Orc6-humansupporting
confidence: 78%
“…Although it is unusual for a chromatin-associated factor to play a role in spindle organization, it is not unprecedented. For example, origin recognition complex protein 2 (ORC2) and ORC6 have, in addition to their activities at the replication origins, spindle-related functions at the centrosomes and kinetochores, respectively (Prasanth et al, 2002(Prasanth et al, , 2004. DNA repair factors such as BRCA1 were also shown to localize to the centrosomes and play a role in centrosome duplication (Xu et al, 1999;Fukasawa, 2005).…”
Section: Two Distinct Functions Of Cohesin In Mitosismentioning
confidence: 99%
“…Immunostaining of cells with antibodies against ORC6 revealed that a considerable portion of this protein is present in the cytoplasm and is localized to the cell membrane and in the cleavage furrow [20,21]. ORC6 depletion in D. melanogaster cells results in defects in cytokinesis [66].…”
Section: Centrosome Duplication and Cytokinesismentioning
confidence: 99%
“…In the last few decades, involvement of ORC in numerous highly diverse cellular functions was discovered, e. g. the formation of heterochromatin, chromosome condensation and segregation, centrosome duplication, cytokinesis and mRNA nuclear export [1417]. The sub-complexes or the individual subunits of ORC are localized not only in nuclei and on the mitotic chromosomes, but in the cytoplasm as well [1821]. Interestingly, ORC subunits have also been detected in terminally differentiated mammalian cells that do not undergo subsequent cell divisions, for example, cardiomyocytes and neurons [22].…”
Section: Introductionmentioning
confidence: 99%